Boost Your Career With a One AWWA Operator Scholarship. Issue 7 (3rd September 2021) - Hektor, Michelle; Macler, Bruce
Abstract : If you're a water operator wanting to learn more to get ahead and need money to do it, we encourage you to apply for a One AWWA Operator scholarship. Different from a traditional AWWA academic scholarship, a One AWWA Operator scholarship helps fund continuing education for water and wastewater operators and encourages students to enter the field of water operations. The scholarship funds can be used for conference attendance, vocational/technical school, community college or university tuition, or books and materials for continuing education and certification